1994
DOI: 10.1172/jci117238
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone receptor mRNA expression by human pituitary tumors in vitro.

Abstract: An important question in the pathogenesis and regulation of human gonadotroph adenomas is whether heterogeneous gonadotropin responses to gonadotropin-releasing hormone (GnRH) are due to dysregulation of GnRH receptor biosynthesis and/ or cell-signaling pathways. We investigated gonadotropin responsiveness to pulsatile GnRH in 13 gonadotroph adenomas. All tumors had evidence of follicle-stimulating hormone (FSH) ft and a subunit biosynthesis using reverse transcriptase/polymerase chain reaction (RTPCR) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 42 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…This distribution of GnRHR well reflects that found in normal pituitary cells, with the exception of thyrotroph adenomas. Our immunohistochemical results concerning the distribution of GnRHR correlate well with the expression of GnRHR mRNA in pituitary adenomas as detected by ISH, RT-PCR, and in situ RT-PCR (IS-RT-PCR), with the exception of ACTH-secreting tumors [1,24,26] (Table 3). In fact, the cases of functioning and nonfunctioning corticotroph adenomas that we examined did not show a GnRHR IR.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This distribution of GnRHR well reflects that found in normal pituitary cells, with the exception of thyrotroph adenomas. Our immunohistochemical results concerning the distribution of GnRHR correlate well with the expression of GnRHR mRNA in pituitary adenomas as detected by ISH, RT-PCR, and in situ RT-PCR (IS-RT-PCR), with the exception of ACTH-secreting tumors [1,24,26] (Table 3). In fact, the cases of functioning and nonfunctioning corticotroph adenomas that we examined did not show a GnRHR IR.…”
Section: Discussionsupporting
confidence: 68%
“…The high incidence of GnRH and GnRHR gene expression, found in pituitary adenomas with special reference to gonadotropin-secreting and nullcell adenomas, suggests that locally produced hypothalamic hormones and related receptors may play a role in the regulation of tumor cell growth and function, acting through a paracrine/autocrine mechanism. FSH/LH adenomas showing diffuse IR for GnRHR (7 of 12 of our cases) may correspond to those gonadotroph tumors that are responsive to pulsatile GnRH in vitro and show normal tumor receptor biosynthesis [1]. On the contrary, the FSH/LH adenomas lacking GnRHR IR (5/12 of our cases) may correspond to the subset of gonadotroph tumors with GnRHR biosynthetic defects and GnRH unresponsiveness, described by Alexander and Klibansky [1].…”
Section: Discussionmentioning
confidence: 62%
“…Alexander et al (13) and Miller et al (14) found GnRH and GnRH-R mRNAs in nontumorous and neoplastic human pituitaries by in vitro experiments and the PCR technique. These reports, however, did not investigate gene expression at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al (13) detected GnRH-R mRNA in human pituitary adenomas in vitro. In addition, using PCR techniques, Miller et al (14) reported both GnRH and GnRH-R mRNAs in gonadotroph tumors, as well as in the normal human pituitary.…”
mentioning
confidence: 99%
“…This theory has been given support by recent studies. Firstly, gonadotroph adenomas that did not respond to gonadotrophin-releasing hormone (GnRH) showed no evidence of expression of GnRH-receptor mRNA (Alexander and Klibanski, 1994). In addition, in patients with lactotroph adenomas, which are resistant to the dopamine agonist, bromocriptine (i.e., prolactin levels are not reduced by the drug), the level of D2 dopamine receptor expression is lower than in patients who do respond (Caccavelli et al, 1994;Pellegrini-Bouiller et al, 1996).…”
Section: Expression Of Receptorsmentioning
confidence: 99%